Conservation agriculture saves irrigation water in the dry monsoon phase in the Ethiopian highlands - Belay, Sisay A.; Schmitter, Petra S.; Worqlul, Abeyou W.; Steenhuis, Tammo S.; Reyes, Manuel R.; Tilahun, Seifu A. (MDPI, 2019)
Water resources in sub-Saharan Africa are more overstressed than in many other regions of the world. Experiments on commercial farms have shown that conservation agriculture (CA) can save water and improve the soil. Nevertheless, its benefits on smallholder irrigated farms have not been adequately investigated, particularly in dry monsoon phase in the Ethiopian highlands. We investigated the effect of conservation agriculture (grass mulch cover and no-tillage) on water-saving on smallholder farms in the Ethiopian highlands. Irrigated onion and garlic were grown on local farms. Two main factors were considered: the first factor was conservation agriculture versus conventional tillage, and the second factor was irrigation scheduling using reference evapotranspiration (ETo) versus irrigation scheduling managed by farmers. Results showed that for both onion and garlic, the yield and irrigation water use efficiency (IWUE) was over 40% greater for CA than conventional tillage (CT). The soil moisture after irrigation was higher in CA compared with CT treatment while CA used 49 mm less irrigation water. In addition, we found that ETo-based irrigation was superior to the farmers’ irrigation practices for both crops. IWUE was lower in farmers irrigation practices due to lower onion and garlic yield responses to overirrigation and greater water application variability.